Mechanical characterization of ancient Portuguese riveted bridges steels. Issue 4 (2nd October 2017) - Raposo, Patrícia; Correia, José; Lesiuk, Grzegorz; Valente, Isabel; De Jesus, Abílio; Calçada, Rui
Abstract: In repairing and retrofitting processes of ancient riveted steel bridges is crucial to assess the structural state of old metals to guaranty structural safety. Metals under long-time operations (mild, rimmed low carbon steels <0.1% C, puddle irons) and cyclic loading present a tendency for degradation processes. The case-studies of this work are five metallic bridges existing in Portugal (Luiz I, Eiffel, Fão, Pinhão and Trezói). This work presents the study of some characteristics of materials extracted from the five case-studies, such as: monotonic tensile strength, chemical composition, microstructures, hardness, notch toughness and fatigue crack propagation. In terms of monotonic tensile tests, the materials from Luiz I, Eiffel and Fão bridges are similar to puddle steel and the materials from Pinhão and Trezói bridges are similar to mild steel. In terms of toughness only the material from the Pinhão bridge exhibits acceptable toughness properties, considering current design requirements. The materials from the other bridges exhibit relatively low toughness properties. The fatigue crack propagation data from the old Portuguese riveted steel bridges were correlated using the Paris's law and the possibility for a design crack growth rate was discussed.